2019
DOI: 10.3390/coatings9020103
|View full text |Cite
|
Sign up to set email alerts
|

Current Progress on the Surface Chemical Modification of Carbonaceous Materials

Abstract: Carbon-based materials is considered one of the oldest and extensively studied research areas related to gas adsorption, energy storage and wastewater treatment for removing organic and inorganic contaminants. Efficient adsorption on activated carbon relies heavily upon the surface chemistry and textural features of the main framework. The activation techniques and the nature of the precursor have strong impacts on surface functionalities. Consequently, the main emphasis for scientists is to innovate or improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(49 citation statements)
references
References 185 publications
(157 reference statements)
1
47
0
1
Order By: Relevance
“…As a porous carbonaceous adsorbent, AC has a better sorption ability than other adsorbents, and thus its energy consumption during regeneration is relatively low, which is why it is the main adsorbent used in industrial adsorption [5]. Nowadays, enormous research effort is devoted to modifying the surface and pore structures of activated carbon in order to enhance its adsorption capacity for CO 2 [6][7][8]. However, AC as an adsorbent presently exhibits low CO 2 adsorption selectivity, especially in the presence of water vapor in the flue gas [9].…”
Section: Introductionmentioning
confidence: 99%
“…As a porous carbonaceous adsorbent, AC has a better sorption ability than other adsorbents, and thus its energy consumption during regeneration is relatively low, which is why it is the main adsorbent used in industrial adsorption [5]. Nowadays, enormous research effort is devoted to modifying the surface and pore structures of activated carbon in order to enhance its adsorption capacity for CO 2 [6][7][8]. However, AC as an adsorbent presently exhibits low CO 2 adsorption selectivity, especially in the presence of water vapor in the flue gas [9].…”
Section: Introductionmentioning
confidence: 99%
“…This showed the region of the mixtures (center of the figure, dark green square) and the edges where the pure solvents were. For the pure solvents, the intensity of the interaction was greater with toluene than hexane (it increased 2.5 times for CS and it doubled for CST); this occurred because both showed London dispersion interactions, which were originated between an adjacent pair of atoms or molecules when they were in close proximity and they were attractive forces between non-polar organic molecules (Mantri et al, 2017), such as hexane and toluene; but toluene, in addition to causing this type of forces, generated π-π interactions between its aromatic ring and the delocalized π electrons of the graphene layers of the activated carbon (Rehman et al, 2019;Rubahamya et al, 2019). Besides, the methyl group of toluene is an electron-donating group which also contributed to increasing the electronic density of the ring (Bazzini and Wermuth, 2015) and then, the interaction with the πē of the graphitic surface of the porous solid.…”
Section: Adsorbateadsorbentmentioning
confidence: 99%
“…These results are corroborated by those reported in the literature. In fact, many studies reported that nitric acid treatment reduces the specific surface area (Soudani et al 2013, Bernal et al 2018, Rehman et al 2019. Soudani et al 2013 reported that this reduction depends on the concentration of HNO 3 .…”
Section: Surface Morphology and Surface Areamentioning
confidence: 99%